Investigating the repair of cracks through bacterial self-healing for sustainable concrete in aggressive sulfate attack environments - Seleem Ahmad; Yasmine Elmenshawy; Yasser Osman El Gammal; Hamees Mohamad El-Sheikh; Mohamed Moawad; Ahmed A. Elshami; Mohamed A.R. Elmahdy (Fracture and Structural Integrity)
Concrete completely submerged in sulfate solutions has been used as the primary study subject for the durability of concrete subjected to sulfates. On the other hand, empirical data from the field indicates that concrete exposed to sulfates may exhibit physical attack-induced surface scaling above. This study aims to study the two different types of local bacteria, (BS) and (BM), with content of 0%, 0.25%, 1%, 2.50%, and 5.00% by cement weight used in this work under curing in sulfate to examine the efficiency of bacterial self-healing of cracks for sustainable concrete in aggressive sulfate attack environments. The results show that in both curing in freshwater, FW, and sulfate, SUL, the optimum bacteria ratio was 2.5% BM, and the compressive strength improved by 43.34% for FW and 47.65% for sulfate. On the other hand, the results proved that the crack-filling and crack-repairing methods may be considered quicker than conventional methods. Moreover, a detailed conclusion about the preparation and processing of bacteria to provide the most significant content of locally accessible bacteria in Egypt, mainly when using chemical and mineral additives.